2015
DOI: 10.1016/j.sdentj.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of specific dental anomalies in a group of Saudi cleft lip and palate patients

Abstract: Dental anomalies were common in Saudi subjects with CLP type. This will complicate the health care required for the CL/P subjects. This study was conducted to epidemiologically explore the prevalence of dental anomalies among Saudi Arabian subjects with CLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 41 publications
(60 reference statements)
4
37
0
Order By: Relevance
“…Studies conducted in different populations worldwide have reported that dental anomalies are more prevalent in patients with NSCLP than in those without NSCLP. For example, lateral incisor agenesis and microdontia in Saudi Arabia and tooth impaction in Brazil are more prevalent in patients with NSLCP (Paranaiba et al, 2013; Al-Kharboush et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different populations worldwide have reported that dental anomalies are more prevalent in patients with NSCLP than in those without NSCLP. For example, lateral incisor agenesis and microdontia in Saudi Arabia and tooth impaction in Brazil are more prevalent in patients with NSLCP (Paranaiba et al, 2013; Al-Kharboush et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…5 In Saudi Arabia, Al-Kharboush et al found that two-thirds of their unilateral CLP sample had at least one missing tooth. 7 Dental age is one of the three designations of physiological maturity, besides skeletal age and somatic age. An accurate estimation of dental age is a key tool in forensic dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Although congenitally and/or developmentally missing teeth are seen in individuals with CLP, 8 12 this type of dental anomaly varies according to ethnicity, cleft type, and gender. 13 17 Cleft width, arch form, and shape of nasal septum can give information about lateral incisor agenesis.…”
Section: Introductionmentioning
confidence: 99%